PENGARUH KECAKAPAN MEDIA (MEDIA LITERACY) TERHADAP TERBANGUNNYA KEWARGAAN AKTIF (ACTIVE CITIZENSHIP) (STUDI PADA SISWA SMA WIDYAGAMA DAN SMKN 4 KOTA MALANG) - Molyo, Priyo Dari (Jurnal Nomosleca, 2016)
Abstract Media function as the fourth pillar of democracy when they cover and present news in an objective, neutral, and balanced manner. Nevertheles, media never operated in vacuum in carrying out the duties. Neither, media did so purely to serve public interest. But, media did the the job to serve certain economic and political interest simultenously. This of course will block the way for the current undergoing democratization process. To make the case even worse, media become an integral part of the society life in which they were saturated by media industry. As such, media literacy which equipped citizens which skills such as access, analysis, evaluation, and creation played a strategic role to empower citizen to actively take part in their social and political life. This is due to the fact that through media literacy citizen will acquire critical thinking and self expression skills which are necessary requirement to be active citizen. This article attempts to explore the influence of media literacy on active citizenship among student of Widya Gama private-owned and State Senior High Vocational School IV Malang City. Employing quantitative survey method, the research found a great impact of media literacy on active citizenship among grade two of the above said school students.DOI :Â https://doi.org/10.26905/nomosleca.v2i1.378